The Design of the Problem Analysis-Based E-Teaching Materials for the Tahsin Al-Quran Course - Masyhudi, Fauza; Zukdi, Ilpi; Frasandy, Rendy Nugraha; Alfurqan, Alfurqan; Khairat, Annisaul (Ta'dib, 2024)
This paper aims to produce a product designed based on problem analysis in learning The Tahsin Al-Quran course at the Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program, Faculty of Tarbiyah and Teacher Training, UIN Imam Bonjol Padang. This research is development research using the ADDIE model at the analysis and design stage. Data on The Tahsin Al-Quran lecture problems have been obtained from questionnaires, interviews and observations carried out at the problem analysis stage. This research reveals the important steps taken in designing e-teaching material product. This research has found the ways to design the problem analysis based e-teaching materials  to make it easier for the students to reach the goal of The Tahsin Al-Quran learning.